Sequential Serous Choroidal Detachment in Subjects Undergoing Bilateral Trabeculectomy - Maryam Yadgari; Kiana Hassanpour; Fatemeh Vafaei; Nina Firoozian; Maryam Oraee Yazdani; Zahra Khorram; Sadid Hooshmandi (Journal of Ophthalmic & Vision Research)
Purpose: This study aims to assess the incidence of serous choroidal detachment (SCD) in the second eye of patients undergoing bilateral trabeculectomy (BT) and evaluate its impact on the clinical outcomes and failure rate of trabeculectomy in the second-operated eyes. Methods: This retrospective case–control study analyzed 90 eyes of 45 patients who underwent BT. Surgical success was defined as maintaining intraocular pressure (IOP) between 5 and 21 mmHg, requiring no additional glaucoma surgery, and exhibiting a visual acuity of at least light perception. Relevant patient data, such as age, glaucoma type, systemic diseases, preoperative and postoperative IOP, and complications, were extracted from medical records. Results: The mean age of patients was 59.8 ± 11.1 years. The five-year cumulative probability of success in the first- and second-operated eyes was 61.0% and 67.6%, respectively (log rank = 0.085, P = 0.77). Among the participants, 28.9% experienced SCD, and 76.9% of those who had SCD in the first-operated eye developed the same condition in the second eye as well (P < 0.001). In the first-operated eyes, the five-year cumulative probability of survival was 71.7% without SCD and 35.0% with SCD (log rank = 2.59, P = 0.107). Conclusion: The occurrence of SCD in the first eye following trabeculectomy may indicate a predisposition to its development in the second eye during BT. Furthermore, the surgical success rate of the second-operated eye is comparable to the outcomes of the first eye undergoing BT.